Awareness on the adverse effects of vaping to health among university students in UTAR - Lim, Yu Hui (2022)
Background and Objective: Nowadays, vaping had become popular, especially among the young generation. Vaping was an action of breathing in and out nicotine or other drugs in a state of vapour rather than smoking by using electronic cigarettes or other devices. Like tobacco cigarettes, e-cigarettes would bring adverse effects on human health. Most commonly, people who vaped would suffer from coughing, irritation in the mouth and throat, cough, nausea and vomiting. Besides, vaping would also harm the body system such as respiratory system, cardiovascular system, oral cavity, gastrointestinal system, neurological system and haematopoietic system. Till 2020, 33.7% of Malaysian claimed to have vaped. The result showed that the Malaysian’s vaping rate was relatively high, and this issue should be investigated seriously. Hence, the aim of this study was to determine the awareness of university students towards the adverse effects of vaping on health and to determine the prevalence of vaping among university students in UTAR. Methods: A descriptive cross-sectional study is carried out among university students in UTAR. A self-administered questionnaire will be distributed to the students online to determine the prevalence of vaping among university students and the awareness towards the adverse effects of vaping on health. 416 participants who aged between 18 to 25, foundation and undergraduate students from UTAR Sungai Long and Kampar, will be recruited to fill up the questionnaire. All the data collected from the Microsoft Form will be computerised and analysed by using IBM Statistical Package for Social Science (SPSS) Statistics 26 software. The study outcomes will be produced by using Microsoft Excel. Descriptive statistics will analyse demographic data. Results: The total number of respondents was 433 students, but only 422 of those responses were processed. There are 206 male participants (48.8%) and 216 male participants (51.2%), with a mean age of 19.89 (SD = 1.45). 3.3% of UTAR students reported that they currently vaped, which was significantly higher among males than females (78.6% vs 21.4%). All the participants had an overall average score of 25.76 (SD = 10.28) out of a total score of 47 on vaping awareness. 24.6% of the respondents considered as having awareness while 75.4% of the respondents considered as no awareness, with the scores falling below the cut-off point. Conclusion: In short, every authority can plan for future programmes or education to help decrease the prevalence of vaping and increase university students’ awareness towards the effects of vaping on human health. More attention must be given to the usage of e-cigarettes among adolescents before this trend rises. Future study can be conducted on a larger population which include all university students in Malaysia.